Impact of Helicobacter pylori infection on neoadjuvant chemotherapy in locally advanced gastric cancer: a retrospective analysis - Bin Zhong; Zhizhong Xiong; Jiabo Zheng; Saddam Ahmed Mohamed; Jiachen Sun; Dayin Huang; Zijian Deng; Jianping Guo; Junsheng Peng; Huashe Wang; Lei Lian (BMC Cancer)
Abstract Background Helicobacter pylori (H. pylori) infection may affect the efficacy of immunotherapy and adjuvant chemotherapy in gastric cancer patients. However, the role of H. pylori infection in neoadjuvant chemotherapy in patients with locally advanced gastric cancer (LAGC) remains unclear. This study investigated the effect of H. pylori infection on neoadjuvant chemotherapy and prognosis of patients with LAGC. Methods This retrospective study utilized data from patients with LAGC who underwent neoadjuvant chemotherapy and surgical treatment at the Sixth Affiliated Hospital of Sun Yat-sen University from January 1, 2010, to January 31, 2021. Patients were grouped according to their H. pylori infection status. The responses of the two groups to neoadjuvant chemotherapy and oncological outcomes were then compared. Results A total of 239 patients were included in the analysis, and the baseline characteristics of the H. pylori-positive (n = 51) and H. pylori-negative (n = 188) groups were comparable. Further analysis revealed that H. pylori infection was significantly associated with the major pathological response (P = 0.009). Multivariate analysis showed that factors related to major pathological response included; age ≤ 50 (OR: 0.423, 95% CI: 0.194–0.925), H. pylori infection (OR: 0.396, 95% CI: 0.183–0.854), pathological stage T 3/4 (OR: 0.524, 95% CI: 0.288–0.954), and CA12-5 > 35 U/mL (OR: 0.345, 95% CI: 0.132–0.904). Both overall survival (OS) and disease-free survival (DFS) rates were poorer in the H. pylori-positive group than in the H. pylori-negative group (OS: Log-Rank P = 0.035; DFS: Log-Rank P = 0.029). Conclusion This cohort study indicated that H. pylori infection may be associated with tumor response to neoadjuvant chemotherapy and survival outcomes in patients with LAGC.